Penerapan Manajemen Waktu dan Penerapan Konseling Individu untuk Mengurangi Prokrastinasi Akademik di SMK Miftahul Huda Kendal - Safaat Yulianto; Atika Nurani Ambarwati; Zakaria Bani Ikhtiyar; Adiyah Mahiruna (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
According to Ferrari in his 2012 research, it was explained that academic procrastination is a type of procrastination carried out on types of formal tasks related to academic assignments, which can be school assignments or course assignments. One of the characteristics of academic procrastination is the time gap between plans and actual performance. In this research, it is proposed to disseminate time management to guidance and counseling teachers and female students regarding time management for students who are very active on social media. In research (Rifa'i and Syahrina 2019), the elements put forward by Zimmerman in his research on self-regulated learning are explained, with these elements students are able to decide for themselves or with the help of others, what their needs are, how to set targets. learning, what strategies will be used in completing academic assignments and being able to monitor one's own progress. Counseling guidance for students is expected to help students find out their own progress.